Long-term assessment of Helicobacter pylori cagA EPIYA motif changes and pathology outcomes in gastric biopsies of dyspeptic patients: 10-year follow-up - Paria Ghadersoltani; Shahrzad Shoraka; Alireza Sadjadi; Parastoo Saniee (BMC Gastroenterology, 2024)
Abstract Introduction Helicobacter pylori exhibit considerable genetic diversity, especially in the cagA gene, which is prone to rearrangement, affecting gastric pathology. This study aims to identify changes in the cagA EPIYA motif patterns and gastric pathology during long-term colonization and to explore how factors such as smoking, alcohol consumption, gender, and age influence these changes. Methods Paired formalin-fixed paraffin-embedded (FFPE) gastric biopsies from 100 H. pylori-positive patients with digestive disorders obtained 10 years apart. After DNA extraction, the presence of H. pylori was detected by PCR amplification of the 16 S rRNA gene, and the cagA gene and its EPIYA motif patterns were identified by PCR using specific primers. Results Our results showed that 90% and 91% of primary and secondary samples were cagA positive respectively. The most frequent patterns were AB and ABC, and in 52% of patients, notable changes occurred in the motif pattern of cagA. The most frequent gastric pathology was chronic inflammation in both sets of samplings and in 45% of patients, changes in pathology outcomes were reported. A significant association was found between changes in pathology outcomes and gender (P = 0.01), with alterations observed in 24 male patients and 21 female patients, and between changes in pathology outcomes and smoking (P = 0.00). Among those with changes in pathology outcomes, only 18 patients had smoking habits, indicating a potential inverse correlation between smoking and the observed changes. A logistic regression analysis was performed to examine the association between smoking, gender, changes in cagA and alterations in gastric pathology. The finding revealed no significant relationship with smoking (P = 0.978 OR = 1.012) and gender (P = 0.901, OR = 0.950), but identified a significant association with changes in the cagA gene (p = 0.001, OR = 0.296), Conclusion he study highlights substantial heterogeneity in the cagA EPIYA motif patterns in long-term H. pylori colonization and notes an inverse relationship between pathology outcomes and smoking, warranting further investigation.